How CNN Arabic Retains Power in its 'Gaza Solidarity Encampment' Coverage: A Social Actors Approach - Kalila Nooraya Sugarda; Fahmy Lukman; Tubagus Chaeru Nugraha (UIN Sunan Gunung Djati, 2025)
The Palestinian movement landscape has seen a tremendous rise following the rising death toll in Gaza. Among the loudest voices have been US campuses' student protests against their government and academic institutions' complicity in the war. In the face of the public opinion shift, this qualitative descriptive study aims to unravel how CNN Arabic maintains discursive power in its coverage of the pro-Palestinian protests. Focusing on CNN Arabic's initial reporting of the 'Gaza Solidarity Encampment,' this study analyzes the data by applying Theo Van Leeuwen's critical discourse analysis framework, specifically the Social Actors Approach. By utilizing this framework, the author examines CNN Arabic's representation of social actors in its narrative, exploring both their exclusion and inclusion. In light of the results, the author categorizes the data into three categories: the representation of (1) Columbia students, (2) the Columbia University president and critics, and (3) external actors. The results demonstrate CNN Arabic's elaborate use of both exclusion and inclusion strategies. Inclusion strategies were used repeatedly to marginalize student protesters and the university president, as well as to establish the credibility of external sources. On the other hand, exclusion strategies were used much less, primarily to divert readers' attention from the real issue and protect critics of the protests. By employing these strategies, CNN Arabic is able to maintain its discursive power, regain public influence, and convey negative sentiments toward the pro-Palestinian protesters.